Electric-field control of magnetic properties for amorphous Fe2O3/LiTaO3 thin film. Issue 43 (22nd October 2018) - Cheng, Bin; Qin, Hongwei; Zhang, Zhongli; Liu, Weikang; Miao, Tingting; Xie, Jihao; Liu, Liang; Zhou, Guangjun; Hu, Jifan
Abstract : Amorphous-Fe2 O3 /LiTaO3 film can exhibit weak ferromagnetism, which may arise from some inhomogeneous, non-collinear, ferromagnetic ordered clusters with short range order. Abstract : Amorphous-Fe2 O3 /LiTaO3 film can exhibit weak ferromagnetism, which may arise from some inhomogeneous, non-collinear, ferromagnetic ordered clusters with short range order. A perpendicular electric field acting upon amorphous-Fe2 O3 /LiTaO3 film could adjust its magnetic properties at 300 K. The saturation magnetization ( M s ) of amorphous-Fe2 O3 /LiTaO3 film could be enhanced by a positive electric field and reduced by a negative electric field. The change induced by an electric field, which was reversible and non-volatile, may be connected with the migration effects of Li + . The oscillation of the curve for the M s dependent on the voltage may reflect complicated processes. These remarkable and important findings may inspire more in-depth research, and lead to an alternative approach to future magneto-electronic devices.